RISK FACTORS OF HYPERTENSION - Nuraini, Bianti (Majority, 2015)
Abstract Hypertension is defined an increasing blood pressure more than normal value or as a systolic blood pressure of 140 mmHg or more, or a diastolic blood pressure of 90 mmHg or more. According to the American Society of Hypertension (ASH), Hypertension is a syndrome or collection symtoms that influences of progressiveness a cardiovascular problem, the collection symtoms are result from many interconected condition such as aging process, because of hypertension is an interaction of multiple genetic and environmental factors.The complication of hypertension is do toe uncontrolled high blood pressure, in which can lead to heart attack or coronary artery deseases, heart failure, stroke, kidney desease and retinopaty. Although the etiologies of hypertension are not clear yet, but the impact of hypertension was very dangeorous for an incresing mortality and morbidity, so that hypertension called “the silent killer”. Several factors are known to cause hypertension consist of causal factors that can be modified (diet, obesity, smoking, diabetes and diseases) and the causes that can not be modified (age, ras, sex and genetic). Keywords : Hypertension, various factors of hypertension Abstrak Hipertensi merupakan penyakit peningkatan tekanan darah di atas nilai normal. Menurut American Society of Hypertension (ASH), hipertensi adalah suatu sindrom atau kumpulan gejala kardiovaskuler yang progresif akibat dari kondisi lain yang kompleks dan saling berhubungan. Komplikasi yang dapat terjadi akibat hipertensi adalah penyakit jantung koroner, gagal jantung, stroke, gagal ginjal kronik, dan retinopati. Penyebab terjadinya hipertensi sampai saat ini belum dapat dipastikan, namun dampak dari hipertensi mengakibatkan morbiditas yang memerlukan penanganan serius, dan mortalitas yang cukup tinggi sehingga hipertensi disebut sebagai “the silent killer”. Beberapa faktor yang diketahui menyebabkan terjadinya hipertensi terdiri dari faktor penyebab yang dapat dimodifikasi (diet, obesitas, merokok, dan penyakit DM) dan faktor penyebab yang tidak dapat dimodifikasi (usia, ras, jenis kelamin dan genetik). Kata Kunci : Hipertensi, berbagai faktor terjadinya hipertensi